The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s44172-022-00016-5
|View full text |Cite
|
Sign up to set email alerts
|

Wireless light energy harvesting and communication in a waterproof GaN optoelectronic system

Abstract: Wireless technologies can be used to track and observe freely moving animals. InGaN/GaN light-emitting diodes (LEDs) allow for underwater optical wireless communication due to the small water attenuation in the blue-green spectrum region. GaN-based quantum well diodes can also harvest and detect light. Here, we report a monolithic GaN optoelectronic system (MGOS) that integrates an energy harvester, LED and SiO2/TiO2 distributed Bragg reflector (DBR) into a single chip. The DBR serves as waterproof layer as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…The EL and responsivity spectra show an approximate 50 nm wavelength overlap for the response to higher-energy photons, suggesting that the QW diode can detect and modulate photons emitted by itself. Two diodes sharing identical QW structures can be separately used as a transmitter and a receiver to form a wireless light communication system. Gao et al monolithically integrated different diodes with identical QW structures into a single chip to produce a waterproof optoelectronic system, in which the QW diodes acted as a transmitter, a receiver, and an energy harvester. In particular, the simultaneous emission-detection phenomenon occurs when we shine a shorter-wavelength light beam onto the device and apply a forward voltage to it at the same time, providing a number of promising applications from full-duplex light communication to simultaneous illumination imaging.…”
Section: Resultsmentioning
confidence: 99%
“…The EL and responsivity spectra show an approximate 50 nm wavelength overlap for the response to higher-energy photons, suggesting that the QW diode can detect and modulate photons emitted by itself. Two diodes sharing identical QW structures can be separately used as a transmitter and a receiver to form a wireless light communication system. Gao et al monolithically integrated different diodes with identical QW structures into a single chip to produce a waterproof optoelectronic system, in which the QW diodes acted as a transmitter, a receiver, and an energy harvester. In particular, the simultaneous emission-detection phenomenon occurs when we shine a shorter-wavelength light beam onto the device and apply a forward voltage to it at the same time, providing a number of promising applications from full-duplex light communication to simultaneous illumination imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 For a QW diode, the EL spectrum partially overlaps with the responsivity spectrum, which is crucial to establish TDM VLC using two identical QW diodes. In reality, the QW diode can only detect, modulate and harvest shorter-wavelength light than that emitted by itself [22][23][24], which means that an irreversible process exists between light emission and detection of the device. It's of great interest to investigate the underlying mechanism of the dual emissiondetection characteristics and to answer what creates the partial spectral overlap.…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Zhu et al discussed and summarized the recent two-dimensional materials. These studies involve biology, materials science, electronics, chemistry, and other disciplines, and an increasing number of studies are leading the development of modern display technology to a new stage. However, there is seldom a way to give consideration to the advantages of both cost and versatility, which is a pain point and a blind spot for the current development of smart displays. , The development of the next generation of intelligent displays urgently requires dual-function devices. , Oh et al reported a double heterojunction nanorod device that can be used for simultaneous light emission and detection. Using a bifunctional perovskite diode, Shan et al proposed a bidirectional optical link between two identical devices.…”
Section: Introductionmentioning
confidence: 99%